Exploring the uptake and integration of emerging technology into pedagogical practices in Health Sciences Education using an Activity Systems Approach - Doyle, Gregory (School of Education, 2025)
This study investigates integrating educational technology into pedagogy and the role of professional development within a Health Sciences Faculty. It is framed within the interpretivist paradigm and informed by Cultural-Historical Activity Theory (CHAT) and Technological Pedagogical Content Knowledge (TPACK). A systematic literature review followed PRISMA 2020 guidelines to ensure study selection and reporting transparency. The overarching question of why particular lecturers, referred to as BrightSparks, excel in educational technology integration and how they might influence professional development is investigated. Integrating educational technologies in health sciences, with a focus on innovation, remains a challenge for most lecturers. This study defines innovation as the transformative and pedagogically grounded integration of technology to enhance teaching and learning. Hence, this research explores the strategies, challenges, and contextual factors that shape successful educational technology adoption and integration. A sequential mixed methods approach was adopted, with the quantitative component using a Likert-scale online survey and the qualitative component using semi-structured online interviews. Participants were selected based on specific characteristics, particularly their proficiency in using educational technology and identification as potential BrightSparks. Among the 29 participants, 814 professional development activities were attended during the 12 months preceding filling in the survey, with individual attendance ranging from 0 to 60 and an average of about 28 activities per participant. Spearman's rank correlation and the Mann- Whitney U Test examined relationships between scores, demographic characteristics, and formal qualifications. Correlations emerged between academic qualification, teaching experience, and autonomy. The qualitative interviews revealed nuanced social and cultural dynamics influencing educational technology integration. Deductive thematic analysis using CHAT and TPACK, emphasising CHAT as the central framework for analysing BrightSparks' practices, illuminated the complexities of integrating educational technology, pedagogy, and content knowledge and identified contradictions affecting professional development. The combined quantitative and qualitative data derived from BrightSparks emphasised adaptability, agency, student-centredness, transformative pedagogical approaches, and institutional support, corroborated by literature in the field. These findings informed the development of a ‘bottom-up' Knowledge Framework for Technology Transformation (KF4TT), integrating the strengths of CHAT and TPACK to support educational technology integration through professional development in higher education. Essential components of the KF4TT include targeted professional development to enhance individual lecturers' TPACK competencies, institutional support, collaborative learning communities, strategies to address systemic barriers, and encouragement of lecturer agency to foster ownership and flexibility in using professional development. In contrast to traditional professional development models, flexibility, adaptability, and sustainability are key features of the KF4TT, enabling individual lecturers and institutional leaders to continuously review and adapt to rapidly changing educational technology in higher education.